The Past And Present Of Moving Images:Transcending The Boundary Across Departments In The Vocational Higher Education - Mega Iranti; Sihite , Susyentina (Universitas Pendidikan Ganesha, 2024)
Animations were given credentials as an effective medium in various campaigns and public service announcements (PSA). It helps to shape and spread information, frame public attitudes, and ensure the roles and responsibilities. History records how animations were utilized as PSA during WW2 in the form of training content, instructions, propaganda and ideological tools to promote and glorify patriotism. In higher education, animations can be utilized to support the socialization material about quality assurance. An animated PSA in the form of a video explainer was produced as a collaboration between the Quality Assurance (QA) Department and the Animation Study Program of Politeknik Multimedia Nusantara to support project-based learning for semester 2 students. This article aims to link connections between the history of animation as a public service announcement (PSA) with the conduct of project-based learning in vocational institutions, and quality assurance socialization. Descriptions about the history of moving images, project-based learning strategies, and quality assurance socialization are implemented as methodologies to explain the interrelationships among the three. The authors then present a gap analysis regarding the problems in implementing project-based learning faced by the animation study program and the problems faced by the QA department. An action plan is produced to close the gap using existing resources. The result is a descriptive explanation to support the feasibility of how a vocational institution should connect the needs of academic departments and other departments through a collaborative process. In the discussion section, an analysis will be presented of how animation as a medium is capable of transcending the boundaries across departments Keywords: moving image history, animation, project-based learning, quality assurance in education